Financial Literacy and Its Impact on the Income Level of Chili Farmers in Rural Indonesia - Gigih Yudo Sekti; Syafrial; Hery Toiba; Dwi Retnoningsih (HABITAT, 2023)
The financial literacy level determines the economic condition of every social stratum. In other words, when farmers experience failure in regulating their economic activities, it is most likely due to their low financial literacy level. The study aims to identify the financial literacy level of chilli farmers in Rural Areas, analyze the factors that influence the financial literacy level, and analyze the impact of financial literacy on increasing the income of chilli farmers in Rural Areas. This study uses Propensity Score Matching (PSM) method to analyze the impact of financial literacy. The results of the study provide information that (1) The majority of chilli farmers' financial literacy in Rural Areas is at a high level with 65% of the total respondent, (2) The existence of financial literacy in Rural Areas has a positive impact on increasing the income of chilli farmers with a comparison that farmers at high literacy levels have higher incomes of Rp. 65,384,503 compared to farmers who have low literacy levels, and (3) The results of the analysis of factors that influence financial literacy state that the factors of age, education level, land area, land status, farming experience, and family responsibilities have a relationship with financial literacy, but the gender factor cannot be identified statistically.